2013
DOI: 10.1007/s13238-013-3031-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and biochemical studies of human lysophosphatidic acid phosphatase type 6

Abstract: Lysophosphatidic acid (LPA) is an important bioactive phospholipid involved in cell signaling through Gprotein-coupled receptors pathways. It is also involved in balancing the lipid composition inside the cell, and modulates the function of lipid rafts as an intermediate in phospholipid metabolism. Because of its involvement in these important processes, LPA degradation needs to be regulated as precisely as its production. Lysophosphatidic acid phosphatase type 6 (ACP6) is an LPA-specifi c acid phosphatase tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Our results showed that hsa_circ_0013958 improved cell proliferation and invasion at the same time as inhibiting cell apoptosis. hsa_circ_0013958 is located on chromosome 1q21.2 on the plus strand, and it is aligned in a sense orientation to the known protein‐coding gene ACP6 and spans exon 10 . Until now, the function of hsa_circ_0013958 in tumour development and progression was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that hsa_circ_0013958 improved cell proliferation and invasion at the same time as inhibiting cell apoptosis. hsa_circ_0013958 is located on chromosome 1q21.2 on the plus strand, and it is aligned in a sense orientation to the known protein‐coding gene ACP6 and spans exon 10 . Until now, the function of hsa_circ_0013958 in tumour development and progression was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report that mutant p53 upregulates LPA signaling through downregulation of the LPA-degrading enzyme lysophosphatidic acid phosphatase type 6 (ACP6), a lipid phosphate phosphatase. ACP6 is localized to the mitochondria where it plays a role in the regulation of phospholipid levels 22 24 . Although ACP6 expression is decreased in esophageal tumors 25 , its potential roles in tumorigenesis and cancer progression have not been functionally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic prediction of the tertiary structure of Eh HAPp49 by homology-based modeling offered additional insights into its three-dimensional (3D) conformation. Using the Eh HAPp49 polypeptide as the query sequence, a restricted BLAST search of the Protein Data Bank (PDB) repository returned the crystal structures of three protein counterparts as suitable templates (E-value < 10 −14 ) for the 3D modeling: (1) the human PAP (prostatic acid phosphatase): 2HPA, 1CVI, 1ND5, and 1ND6 [ 14 , 15 , 16 ], (2) the human LAP (lysophosphatidic acid phosphatase type 6): 4JOB, 4JOC, and 4JOD [ 17 ], and (3) the Legionella pneumophila HAP: 5CDH [ 18 ]. The top five 3D-models generated by the Modeller multi-template approach met the expected structural benchmarks: low normalized discrete optimized protein energy (zDOPE) score and a Ramachandran plot showing more than 85% of residues in the most favored regions.…”
Section: Resultsmentioning
confidence: 99%